Pengaruh Islamic Religiosity dan Norma Subyektif terhadap Niat Beli Trend Busana Muslim:An Extended of Theory of Reason Action - Sulis Riptiono (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
The development of Muslim fashion business in Indonesia is growing rapidly. It has influencetoward increasingintention to buy consumers on the trend of Muslim fashion. The purpose of this studyis to examineconsumers purchaseintention towardMuslim fashion trend using the extended of Theory of Reason Action (TRA) with the variable Islamicreligiosity. Respondents of the study are Muslim people includes men and women who follow the development ofMuslim fashion trend. Data analysis tools used in this research is by using path analysis. The results showed that thesubjective norms and Islamic religiosityvariables have a positive effect on consumer attitudes on the fashion trend ofMuslims. Subjective norms and consumer attitudes toward the trend of Muslim fashion have a positive effect onconsumer buying intention on the trend of Muslim fashion. The different results are shown in hypothesis testing numberfour which states that Islamic religiosity variable has no significant on consumer buying intention on Muslim fashiontrend, but it can influence indirectly through consumer attitudes on Muslim fashion trend.